The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1136/bmjopen-2022-063697
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study exploring the well-being experiences of paediatric critical care consultants working in the UK during the COVID-19 pandemic

Abstract: ObjectivesThe aim of this study was to examine the well-being experiences of consultants working in paediatric critical care (PCC) settings in the UK during the COVID-19 pandemic.DesignQualitative design using individual interviews and thematic analysis.SettingPCC.ParticipantsEleven medical consultants working in PCC in a range of PCC settings/transport teams in the UK from nine units participated. Participants ranged in years of experience as a consultant from four to 23 years.MethodsA set of open semistructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…54 These are described as basic psychological needs for psychological growth and well-being. 44 Previous research with PCC staff corroborated this theory 30,55 and these concepts were identified in a recent British Medical Association (BMA) report to represent the A-B-C of well-being in medical practice 29 : autonomy/control, belonging and competence.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…54 These are described as basic psychological needs for psychological growth and well-being. 44 Previous research with PCC staff corroborated this theory 30,55 and these concepts were identified in a recent British Medical Association (BMA) report to represent the A-B-C of well-being in medical practice 29 : autonomy/control, belonging and competence.…”
Section: Discussionmentioning
confidence: 88%
“…This study took place in one UK hospital PCC unit. Results may not transfer to other sites or countries but it clearly resonates internationally 30,55,56 . Further research in other countries would help confirm this transferability.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations